14 Days of supplementation with blueberry extract shows anti-atherogenic properties and improves oxidative parameters in hypercholesterolemic rats model. (August 2015) - Ströher, Deise Jaqueline; Escobar Piccoli, Jacqueline da Costa; Güllich, Angélica Aparecida da Costa; Pilar, Bruna Cocco; Coelho, Ritiéle Pinto; Bruno, Jamila Benvegnú; Faoro, Debora; Manfredini, Vanusa
Abstract The effects of supplementation with blueberry (BE) extract (Vaccinium ashei Reade) for 14 consecutive days on biochemical, hematological, histopathological and oxidative parameters in hypercholesterolemic rats were investigated. After supplementation with lyophilized extract of BE, the levels of total cholesterol, low-density lipoprotein cholesterol and triglycerides were decreased. Histopathological analysis showed significant decrease (p < 0.05) of aortic lesions in hypercholesterolemic rats. Oxidative parameters showed significant reductions (p < 0.05) in oxidative damage to lipids and proteins and an increase in activities of antioxidant enzymes such as catalase, superoxide dismutase and glutathione peroxidase. The BE extract showed an important cardioprotective effect by the improvements in the serum lipid profile, antioxidant system, particularly in reducing oxidative stress associated with hypercholesterolemia and anti-atherogenic effect in rats.